Building the Case Against Human Trafficking: Developing and Evaluating a Training Module for Law Enforcement Officials - Sanders, Katie (2015)
Since the passage of federal legislation to address human trafficking in the United States, efforts to measure and combat the crime have continued to grow (Victims of Trafficking and Violence Prevention Act of 2000). Measuring human trafficking has continued to be a difficult task for researchers, law enforcement, and victim services providers. The combined efforts of these groups has lead to the recognition that without more widespread identification of victims and perpetrators of human trafficking—a crime referred to as modern-day slavery—estimates will continue to be inaccurate. In order to improve the identification process, this specific proposal focuses on law enforcement officials. As first responders to crime and the investigative arm of legal proceedings, police officers engage in ongoing training and professional development on a variety of issues. In order to make crimes of human trafficking a part of training for law enforcement, an effective and efficient approach must be available. This paper outlines a training module that could be implemented in the state of Kentucky through a distance, or online, learning option as part of the training already available to law enforcement officials in the state. The online training module is based on a review of literature relevant to designing, delivering, and evaluating effective training. Three learning objectives and appropriate evaluation techniques to measure the objectives lead into recommendations for the implementation of the training. The recommendations also look to contribute to improved measurements of the incidence of human trafficking. Identifying, measuring, and continuing training efforts are all means to understanding and combating crimes of modern-day slavery